2001
DOI: 10.1080/02705060.2001.9663840
|View full text |Cite
|
Sign up to set email alerts
|

A Test of Factors Hypothesized to Influence Biomass of Salmonids in Rocky Mountain Streams

Abstract: Our objective was to determine if salmonid biomass across a large watershed in the Bighorn Mountains of Wyoming was influenced by stream size, channel slope, or abundance of pool habitat. No relationships were observed with wetted width or channel slope; however, a significant relationship was found between biomass and the abundance of pool habitat. These results suggest that geomorphic stream features had little influence on salmonid biomass, but that instream habitat was important. This pattern may occur in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Greater pool habitat has been linked to greater fish abundance and larger fish in various stream systems (Stichert et al 2001;Binns 2004;Harvey et al 2005;Young et al 2005). Our results are consistent with these studies as evidenced by the importance of total pool area in the top models from the model selection exercise, and the results from the regression comparisons.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Greater pool habitat has been linked to greater fish abundance and larger fish in various stream systems (Stichert et al 2001;Binns 2004;Harvey et al 2005;Young et al 2005). Our results are consistent with these studies as evidenced by the importance of total pool area in the top models from the model selection exercise, and the results from the regression comparisons.…”
Section: Discussionsupporting
confidence: 92%
“…For stream pH, numerous lab studies (Ingersoll et al 1990;Mount et al 1990;Cleveland et al 1991;Jagoe and Haines 1997) and field bioassay studies (Gagen et al 1993;Simonin et al 1993;Baker et al 1996;Van Sickle et al 1996;Baldigo and Murdoch 1997;Lachance et al 2000) increase our confidence that low pH and associated dissolution of monomeric aluminum (Al +3 ) influence fish biomass in headwater streams. As noted above, the association of pool habitat with fish biomass has been documented in other correlative studies (Stichert et al 2001;Binns 2004;Harvey et al 2005;Young et al 2005). In addition, studies that manipulate streams to change the amount of pool area and cover have often documented changes in fish biomass (Gowan and Fausch 1996;Jones et al 1996;Riley and Fausch 1995;Solazzi et al 2000;Binns 2004), yet whether such changes are directly attributable to increased productivity or simply increased aggregation or increased immigration is unclear (Gowan and Fausch 1996;Riley and Fausch 1995).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The Riffle Stability Index (RSI) has been used as a sediment metric and is based on the percentage of substrate particles that are smaller than the largest particles entrained in channel‐forming flows (Kappeser, 2002). Riffle stability is important as riffle degradation results in detrimental impacts on the pools used as refugia by many aquatic species (Lisle, 1982; Kruzic et al , 2001; Stitchert et al , 2001). The stability of riffles is also a potentially significant factor in redd scour and the concomitant loss of incubating progeny during high flows, although some work has reported behavioural changes whereby salmonids deposit their eggs below the scour depth or avoid spawning during the periods of increased risk of river bed scour (Montgomery et al , 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Because some species may show an affinity to particular geologic units or elevation ranges, differences in trout biomass across geologic types can be confounded with species composition. For example, Stichert et al (2001) found that brook trout were notably abundant in limestone-derived high-elevation meadow systems in Wyoming. Furthermore, different species may demonstrate different associations with habitat attributes and grazing impacts.…”
Section: Lurking Variablesmentioning
confidence: 99%